Kesamaan Kesempatan Kerja bagi Penyandang Cacat di Sektor Swasta - Firdaus Firdaus (Jurnal HAM, 2012)
National survey data (NSES) in 2003, the number of disabled people in Indonesia as many as 1.67 million people, or 0.8 percent of the entire population of Indonesia. With disabilities as members of society and as citizens of their existence is less well cared for by fellow members of society and government. Of Law. 39 Year 1999 on Human Rights, namely Article 41 paragraph (2) Any claim with disabilities, the elderly, pregnant women, and children, are entitled to obtain facilities and special treatment. Article 42 which states every citizen who are elderly, physically disabled or mentally disabled and entitled to special care, education, training and assistance at the expense of the state, to ensure decent life with dignity, enhance self-confidence and ability to participate in the life society, nation and state. Problem is how to get the right people with disabilities equal opportunity in employment in the private sector? The purpose of this study was to determine the right of persons with disabilities equal opportunity to obtain employment in the private sector.